The Palestinian human right to full Israeli citizenship: Between settler colonialism and a hard place - Samuel, M.T. (Frontiers in Political Science, 2022)
This article examines the significance of a legal analysis supporting the recognition of a Palestinian human right to Israeli citizenship for the advancement of equality in Israel-Palestine. It does so by assessing the workings of Israeli citizenship in accordance with the theoretical frameworks of the nation-state and settler colonialism and in light of the one-state reality. The article demonstrates the importance of treating the two frameworks as complementary, rather than mutually exclusive, in analyses involving Palestinian rights. It argues that the struggle for Palestinian equality is not only a legal one but also a moral one, the success of which depends upon a nuanced understanding of the functioning of law in settler colonialism.